(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2025)
A pot experiment was carried out in the Department of Soil and Environmental Sciences, University of Barishal to evaluate the effects of poultry manure (PM) and inorganic fertilizers on the growth and yield of red amaranth. Eight treatments with three replications were used and the treatment were T1: Control (- RDF & - PM); T2: 100% RDF; T3: 75% RDF + PM 4 t/ha; T4: 75% RDF + PM 8 t/ha; T5: 50% RDF + PM 4 t/ha; T6: 50% RDF + PM 8 t/ha; T7: PM 4 t/ha; and T8: PM 8 t/ha. The treatments were arranged in a completely randomized design. Results showed that poultry manure 8 t/ha along with 50% and 75% recommended doses of fertilizers exerted significant influence at 45 days on the plant height (13.50 cm at 75% RDF), leaf area (75.40 cm2 at 50% RDF), number of leaves (8 at both 50% and 75% RDF), root fresh weight (1.3939 t/ha at 75% RDF), shoot fresh weight (6.4488 t/ha at 75% RDF), leaf fresh weight (5.9602 t/ha at 75% RDF) and yield (1.4853 t/ha on dry weight basis at 50% RDF) of red amaranth. The highest values for most of the parameters at 15, 30 and 45 days of germination were found in treatment T6: (50% RDF + PM 8 t/ha). J. biodivers. conserv. bioresour. manag. 10(2), 2024: 69-78